Diubiquitin-Based NMR Analysis: Interactions Between Lys6-Linked diUb and UBA Domain of UBXN1 - Shahul Hameed, Dharjath; van Tilburg, Gabrielle B. A.; Merkx, Remco; Flierman, Dennis; Wienk, Hans; El Oualid, Farid; Hofmann, Kay; Boelens, Rolf; Ovaa, Huib (Frontiers in Chemistry, 2020)
Ubiquitination is a process in which a protein is modified by the covalent attachment of the C-terminal carboxylic acid of ubiquitin (Ub) to the ε-amine of lysine or N-terminal methionine residue of a substrate protein or another Ub molecule. Each of the seven internal lysine residues and the N-terminal methionine residue of Ub can be linked to the C-terminus of another Ub moiety to form 8 distinct Ub linkages and the resulting differences in linkage types elicit different Ub signalling pathways. Cellular responses are triggered when proteins containing ubiquitin-binding domains (UBDs) recognize and bind to specific polyUb linkage types. To get more insight into the differences between polyUb chains, all of the seven isopeptide-linked di-ubiquitin molecules (diUbs) were prepared and used as a model to study their structural conformations in a solution using NMR spectroscopy. We report the synthesis of diUb molecules, fully 15N-labeled on the distal (N-terminal) Ub moiety and revealed their structural orientation with respect to the proximal Ub. As expected, different diUb molecules exist in different stable conformations in solution, with multiple conformations known to exist for K6-, K48- and K63-linked diUb molecules. These multiple conformations provide structural flexibility in binding with UBDs thereby inducing unique responses. One of the well-known but poorly understood UBD-Ub interaction is the recognition of K6 polyubiquitin by ubiquitin-associated (UBA) domain of UBXN1 in the BRCA-mediated DNA repair pathway. We establish here how a C-terminally extended UBA domain of UBXN1 confers specificity to K6 diUb while the non-extended version of the domain does not show any linkage preference. Using our NMR studies, we show that the two distinct conformations of K6 diUb converge into a single conformation upon binding to this extended form of the UBA domain of the UBXN1 protein. It is likely that more of such extended UBA domains exist in nature and can contribute to linkage-specificity in Ub signalling. The isotopically labelled diUb compounds described here and the use of NMR to study their interactions with relevant partner molecules will help accelerate our understanding of Ub signalling pathways.